Characterization of a Linezolid- and Vancomycin-Resistant Streptococcus suis Isolate That Harbors optrA and vanG Operons - Du, Fanshu; Lv, Xi; Duan, Duan; Wang, Liping; Huang, Jinhu (Frontiers in Microbiology, 2019)
Linezolid and vancomycin are among the last-resort antimicrobial agents to treat infections caused by multidrug-resistant Gram-positive bacteria. Linezolid- and vancomycin-resistant (LVR) Gram-positive bacteria may pose severe threats to public health. In this study, three optrA- and vanG-positive strains were isolated from different farms, which also exhibited resistance to 13 other antibiotics. Mobilome analysis revealed the presence of erm(B), aadE-apt-sat4-aphA3 cluster, tet(O/W/32/O), and vanG on an integrative and conjugative element, ICESsuYSJ17, and erm(B), aphA3, aac(6')-aph(2''), catpC194, and optrA on a prophage, ΦSsuYSJ17-3. ICESsuYSJ17 exhibited a mosaic structure and belongs to a highly prevalent and transferable ICESa2603 family of Streptococcus species. ΦSsuYSJ17-3 shared conserved backbone to a transferable prophage Φm46.1. A novel composite transposon, IS1216E-araC-optrA-hp-catpC194-IS1216E, which can be circulated as translocatable unit (TU) by IS1216E, was integrated on ΦSsuYSJ17-3. Vancomycin resistance phenotype and vanG transcription assays revealed the vanG operon was inducible. The virulence of the LVR strain YSJ17 was less virulent to that of S. suis serotype 2 virulent strain SC070731 in zebrafish infection model. To our knowledge, this is the first report of the co-existence of optrA and vanG operon in Gram-positive bacteria. Since it has been suggested that S. suis may act as an AMR reservoir contributing to the spread of resistance genes to major streptococcal pathogens, the potential dissemination of these resistance genes in S. suis is worrisome and routine surveillance should be strengthened.